Effect of Annealing on Morphological and Functional Properties of Pakistani White Sorghum (Sorghum bicolor) Starch - Tahira Mohsin Ali; Abid Hasnain (Journal of Basic & Applied Sciences, 2016)
The present study reports the effect of annealing on the morphological and functional properties of starch isolated from white sorghum grains. Scanning electron micrographs of native white sorghum starch (NWSS) revealed the presence of spherical and polygonal shaped granules with random distribution of surface pores. The diameter of surface pores ranged between 213-275 nm in NWSS. The size of small and large granules in NWSS ranged between 5-7 µm and 11-21 µm, respectively. There was no significant difference in the size and shape of NWSS and annealed white sorghum starch (AWSS) granules. However, the diameter of surface pores doubled after annealing. The AWSS showed reduced swelling power, solubility and water binding capacity. Pasting temperature increased from 73.4°C in NWSS to 75.8°C in AWSS. The pasting profile of annealed starches showed reduction in peak viscosity, breakdown viscosity, cold paste viscosity and set back viscosity. Paste clarity improved on annealing while, the extent of reduction in percent transmittance after 72 hours of storage was higher for NWSS suggesting use of annealed starch in high clarity products.